Pengaruh Motivasi Dan Gaya Belajar Taruna Terhadap Prestasi Akademik Pada Mata Kuliah Pengantar Ilmu Ekonomi Di Politeknik Penerbangan Surabaya - Silvia, Maulana Anifa; Moonlight, Lady Silk; Furyanto, Faoyan Agus; Musadek, Ahmad; Budiarto , Anton (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study explores the impact of motivation and learning styles on academic achievement in the Introduction to Economics course at Politeknik Penerbangan Surabaya. Despite a rigorous curriculum and effective teaching methods, cadets’ academic performance has not met expectations, raising questions about the internal factors that may influence academic success. The study employs a descriptive quantitative approach, using multiple linear regression to analyze how intrinsic and extrinsic motivation, as well as visual, auditory, and kinesthetic learning styles, affect academic performance. The findings reveal that while motivation has a positive influence on academic achievement, its effect is not statistically significant. Conversely, learning style is found to have a significant impact on academic performance, with the regression analysis showing a stronger influence of learning style (0.702) compared to motivation (0.405). The simultaneous analysis of both motivation and learning style confirms that these factors together account for 85.3% of the variation in academic achievement. These results suggest that teaching strategies should be tailored to match students' learning styles, while also fostering motivation to enhance learning outcomes. The study provides insights for improving educational practices at Politeknik Penerbangan Surabaya and offers actionable recommendations for optimizing cadets' academic success.